PENGARUH PERSONALITY, QUALITY OF WORK LIFE DAN WORK STRESS TERHADAP KINERJA KARYAWAN - Yovita Rian Saputri; Sutianingsih Sutianingsih (ITB AAS Indonesia Surakarta, 2024)
Things like a person's personality, the quality of their work life, and the amount of stress they experience at work are things that can be used to make work better. The aim of this research is to find out how attitudes, quality of work life, and work stress impact the work carried out by BPR Djoko Tingkir Sragen employees. For this research, a questionnaire was used to collect data using quantitative methods and multiple regression. A total of 70 workers answered the questionnaire. Researchers used SPSS version 26 software to analyze this research. This software can show the relationship between independent factors and how much influence personality, quality of work life, and work stress have on how well people do their jobs. It was found that personality, quality of work life, and work stress all have a good and significant influence on how well employees do their work. Keywords: employee performance, personality, quality of work life, work stress.